Real-world analysis of the Celgene Global Drug Safety database: early discontinuation of lenalidomide in patients with myelodysplastic syndromes due to non-serious rash - Weiss L; Gary D; Swern AS; Freeman J; Sugrue MM (Therapeutics and Clinical Risk Management, 2015)
Lilia Weiss,1 Dianna Gary,1 Arlene S Swern,2 John Freeman,1 Mary M Sugrue3 1Global Drug Safety, Celgene Corporation, Summit, 2Biometrics, Celgene Corporation, Berkeley Heights, 3Medical Affairs, Celgene Corporation, Summit, NJ, USA Background: Lenalidomide is approved for treating transfusion-dependent anemia due to lower-risk del(5q) myelodysplastic syndromes (MDS). In clinical trials, rash was common, although severe rash was infrequent. To examine rash in patients with MDS treated with lenalidomide in the real world, the Celgene Global Drug Safety database was analyzed and compared with clinical trials.Materials and methods: Adverse event reports in the post-marketing setting and in the MDS-003/004 clinical trials were analyzed by action taken with lenalidomide, seriousness/grade, time to onset, and treatment duration.Results: Globally, 16,942 reports representing 36,793 adverse events from the post-marketing setting were submitted to the Global Drug Safety database between December 27, 2005 and June 13, 2013. Most rash adverse events were non-serious (Global Drug Safety database, 91%) or grade 1/2 (MDS-003/004 trials, 87%–93%). Unexpectedly, rash, occurring at a median of 9 days after treatment initiation, was the leading cause of permanent discontinuation of lenalidomide. Seventy-two percent of non-serious rash adverse events led to early permanent discontinuation within two cycles, while in the MDS-003/004 pivotal clinical trials, only 2%–3% of rash adverse events led to permanent discontinuation.Conclusion: Non-serious rash was the most common reason for permanent discontinuation of lenalidomide in real-world settings. Managing lenalidomide-related rash using published recommendations might improve treatment duration and optimize patient outcomes. Keywords: adverse events, safety, post-marketing setting